Prevalência e fatores de risco de depressão em pacientes cronicamente infectados pelo vírus da hepatite C - Moretto, Rita [UNIFESP] (2018)
Introduction: Hepatitis C virus (HCV) infection remains a major public health challenge. According the World Health Organization (WHO) an estimate 71 million people were living with HCV infection in 2015, which represents 1% of the world population. Unidentified infected patients will not be treated and thus have the potential to develop cirrhosis and hepatocellular carcinoma. In addition to the hepatic consequences of chronic HCV infection, extrahepatic manifestations including neurologic and psychiatric disturbances may reach 50% with impact in patients´ qualityoflife. Objective: to assess the prevalence and risk factors associated with depression, in the absence of treatment, among patients with chronic hepatitis C (CHC) receiving care at the viral hepatitis outpatient services of Escola Paulista de Medicina – UNIFESP and at the Centro de Prevenção e Assistência às Doenças Infecciosas (CEPADI) in the city of São Caetano do Sul. Methods: Crosssectional study to assess the prevalence and risk factors associated with depression using the Beck Depression Inventory (BDI). Patients followed at the two participating centers, aged over 18 years, monoinfected with chronic hepatitis C, with neither neurologic comorbidities nor decompensated cirrhosis, and no antiviral treatment in the past 12 months, were evaluated to determine the sociodemographic and economic conditions before administering the Beck Depression Inventory. The association among depression and sociodemographic and econimc variables was assessed using univariate and multivariate analyses. Results: 271 patients were included, 129 (47.6%) female and 142 (52.4%) male, mean age 50.8 years, 42.8% had less than nine years of schooling, and 55% belonged to socioeconomic classes C/D/E. According to BDI results, 103 (38%) patients had scores consistent with the diagnosis of depression: 52 (19.2%) mild, 46 (17.9%) moderate, and 5 (1.8%) severe depression. The prevalence of depression was higher among patients receiving care at UNIFESP (47.3%) compared to those from CEPADI (33.3%; p = 0.026). However, this difference between Centers was only observed among women, namely 61.4% and 37.6%, respectively (p = 0.01). Prevalence of depression among socioeconomic classes A/B patients was almost twofold lower than those of classes C/D/E (RR = 0.51; 95%CI: 0.320.87). However, after adjusting for sex, socioeconomic class was associated with depression only among women (36.4% vs 77.8%; p = 0.008), and not among men (25.0% vs 37.9%; p = 0.48). Depression was more often detected in patients with less than 9 years of schooling (42.6% vs 28.9%; p = 0.029). This association loses significance when adjusted for socioeconomic class (p = 0.77). Patients with previous psychiatric treatment had more depression ((61.3% vs 35.0%; p = 0.005). Patients was advanced fibrosis (F3/F4) was also associated with depression (45.3% vs 32.6%; p = 0.039). In the final model of multivariate analysis, that includes socioeconomic class, the female sex, previous psychiatric treatment, and socioeconomic classes C/D/E remained independently associated with depression. If socioeconomic class is not included, advanced fibrosis, female sex, and previous psychiatric treatment remained in the final model. Conclusions: The prevalence of depression in HCC patients with no current treatment was far greater (38.0%) than in the general population. Depression was independently associated with female sex, previous psychiatric treatment, socioeconomic class C/D/E and advanced fibrosis (F3/F4).